2013
DOI: 10.1530/joe-12-0568
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin prevents islet ischemia–reperfusion injury through the COX2–TNFα–NF-κB-dependent signal transduction pathway in mice

Abstract: Islets are exceptionally susceptible to ischemia-reperfusion injury, an increased incidence of primary graft nonfunctionality, and b-cell death during a transplant procedure. Therefore, islets require protection during the early stages of the transplant procedure. Based on the beneficial vascular and anti-inflammatory activity of adiponectin, we hypothesize that adiponectin protects islet cells against ischemia-reperfusion injury and graft dysfunction after transplantation. To examine the effects of adiponecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 28 publications
0
25
0
4
Order By: Relevance
“…In addition, adiponectin can inhibit damaged vascular intimal hyperplasia, smooth muscle cell proliferation, and migration to reduce plaque size (Uemura et al, 2013). Animal experiments further confirmed the anti-inflammatory and anti-atherosclerotic effects of adiponectin (Du et al, 2013). Because adiponectin has a variety of biological effects through adiponectin receptors, the adiponectin receptor gene (ADIPOR) may be a susceptibility gene for ischemic stroke.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, adiponectin can inhibit damaged vascular intimal hyperplasia, smooth muscle cell proliferation, and migration to reduce plaque size (Uemura et al, 2013). Animal experiments further confirmed the anti-inflammatory and anti-atherosclerotic effects of adiponectin (Du et al, 2013). Because adiponectin has a variety of biological effects through adiponectin receptors, the adiponectin receptor gene (ADIPOR) may be a susceptibility gene for ischemic stroke.…”
Section: Introductionmentioning
confidence: 95%
“…Simvastatin is a cholesterol-lowering agent that reduces local and systemic inflammatory responses through unknown mechanisms 6 Previous data has suggested that simvastatin blocks the activities of many important proinflammatory cytokines, 7,8 such as TNF-alpha and NF-κB. These cytokines are found to be actively involved in apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that adipoVEGF−/− mice have reduced adiponectin and increased TNFα expression (26). This raises the possibility that the protective effect of adiponectin on inflammatory-mediated apoptosis on pancreatic β-cells (7, 20, 21) may be lost or reduced in adipoVEGF−/− mice, and therefore may explain, at least in part, the reductions in circulating insulin we have observed in our study. It should be noted that this seems to be an adipocyte-specific effect, since circulating basal insulin and glucose have been reported to be unchanged in muscle-specific VEGF deficient mice compared to littermate controls (2).…”
Section: Discussionmentioning
confidence: 77%